Design and Development of a Monkey Repellent Device Based On Ultrasonic Waves at the Engineering Prayer Room, Malikussaleh University - Isma, Aldi Fadilah; Kartika, Kartika; Asran, Asran; Misriana, Misriana (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
The presence of wild monkeys in the Engineering Prayer Room at Malikussaleh University has become a severe problem for cleanliness and worship activities. Monkeys often damage equipment and disturb the comfort of pilgrims, causing material losses and threatening environmental cleanliness. Traditional methods to repel monkeys have proven ineffective for a long time, so technological solutions such as ultrasonic waves are needed. This study looked at the effects of using various ultrasonic frequencies on monkeys at multiple distances to determine their effective range of distraction. The results show higher frequencies cause more significant interference, especially at close range. At 23 kHz and 26 kHz, monkeys were only disturbed at a distance of 1 and 2 meters, without disturbance at 3 and 4 meters. The frequencies 29 kHz and 32 kHz show interference at a distance of 1 and 2 meters, with variations at 29 kHz at 3 meters. At 35 kHz, the monkeys were highly disturbed at 1 meter, disturbed at 2 meters, and slightly disturbed at 3 and 4 meters. The 38 kHz and 41 kHz frequencies cause significant interference at 1 and 2 meters, and interference is still felt at 3 and 4 meters. Thus, using frequencies above 30 kHz has proven effective in driving away monkeys up to a distance of 4 meters, with the highest intensity of interference at a distance of 1 to 2 meters. It is hoped that using ultrasonic technology can maintain cleanliness, safety, and comfort in prayer activities in prayer rooms and demonstrate commitment to sustainable and environmentally friendly solutions.